Circulating microRNA signatures in mice exposed to lipoteichoic acid - Hsieh Ching-Hua (Journal of Biomedical Science, 2013)
Abstract Background Previously, we had identified a specific whole blood–derived microRNAs (miRNAs) signature in mice following in vivo injection of lipopolysaccharide (LPS) originated from Gram-negative bacteria. This study was designed to profile the circulating miRNAs expression in mice exposed to lipoteichoic acid (LTA) which is a major component of the wall of Gram-positive bacteria. Results C57BL/6 mice received intraperitoneal injections of 100 μg of LTA originated from Bacillus subtilis, Streptococcus faecalis, and Staphylococcus aureus were killed 6 h and the whole blood samples were obtained for miRNA expression analysis using a miRNA array (Phalanx miRNA OneArray® 1.0). Up-regulated expression of miRNA targets in the whole blood, serum and white blood cells (WBCs) of C57BL/6 and Tlr2−/− mice upon LTA treatment in 10, 100, or 1000 ug concentrations was quantified at indicated time (2, 6, 24, and 72 h) using real-time RT-PCR and compared with that in the serum of C57BL/6 mice injected with 100 ug of LPS. A significant increase of 4 miRNAs (miR-451, miR-668, miR-1902, and miR-1904) was observed in the whole blood and the serum in a dose- and time-dependent fashion following LTA injection. Induction of miRNA occurred in the serum after 2 h and persisted for at least 6 h. No increased expression of these 4 miRNAs was found in the WBCs. Higher but not significant expression level of these 4 miRNAs were observed following LTA treatment in the serum of Tlr2−/−against that of C57BL6 mice. In contrast, LPS exposure induced moderate expression of miR-451 but not of the other 3 miRNA targets. Conclusions We identified a specific circulating miRNA signature in mice exposed to LTA. That expression profile is different from those of mice exposed to LPS. Those circulating miRNAs induced by LTA or LPS treatment may serve as promising biomarkers for the differentiation between exposures to Gram-positive or Gram-negative bacteria.